Performance Analysis for 3x3 multiple-input multiple-output communication networks - Charnia Iradat Rapa’ (Proceeding International Conference on Information Technology and Business, 2017)
In this paper, we consider the problem of zero-forcing equalizer is studied for 3x3 multiple-input multiple-output communication system in which MIMO source (three antennas) and destination (three antennas) pairs communicate simultaneously. Zero-forcing (ZF) equalizer are employed at destination to maintain lowcomplexity. The resulting expression is simple and easy to compute. The performance analysis of the proposed algorithm is demonstrated through numerical simulations can be significantly improved. Keywords: Multiple-Input Multiple-Output, Zero Forcing, Bit-Error-Rate.